Implementasi Jaringan Failover Menggunakan OSPF Dengan Algoritme Djikstra - Candra Milad Ridha Eislam; Dadang Iskandar Mulyana; Yuma Akbar (Progresif: Jurnal Ilmiah Komputer, 2023)
Companies usually implement OSPF (Open Shortest Path First) routing on a single link as a communication path to the Internet. This is very vulnerable when there is a problem with the link. The problem that is often encountered is when the link is down. To keep the internet connection running, it is necessary to further develop the network communication process by implementing failover. Failover utilizes two links, the first as the main link and the second link as a backup. This paper will simulate the implementation of a failover network using OSPF in the EVE-NG simulation. The results when testing OSPF use the cost value to determine the link selection. The link with the lowest cost value will be used as the main line, while the link with the higher cost value is used as the backup line. When the main connection is interrupted, the connection will switch to the backup. The ping results obtained in the test when the line changed were 21ms; and it only happened two times unreachable, while for browsing traffic there were no problems on the network.Keywords: Internet; failover network; Open Shortest Path First; Djikstra's Algorithm AbstrakPerusahaan biasanya mengimplementaskan routing OSPF (Open Shortest Path First) pada satu single link sebagai jalur komunikasi ke Internet. Hal ini sangat rentan ketika terjadi permasalahan pada link. pPermasalahan yang sering ditemui adalah ketika link down. Untuk menjaga koneksi internet agar tetap berjalan perlu adanya pengembangan lebih lanjut pada proses komunikasi jaringan dengan menerapkan failover. Failover memanfaatkan dua buah link, pertama sebagai main link dan link kedua sebagai backup. Paper ini akan mensimulasikan implementasi jaringan failover menggunakan OSPF pada simulasi EVE-NG. Hasilnya pada saat pengujian OSPF menggunakan nilai cost untuk menentukan pemilihan linknya. Link dengan nilai cost terkecil akan digunakan sebagai jalur utama, sedangkan link dengan nilai cost yang lebih tinggi digunakan sebagai jalur backup. Ketika koneksi utama terganggu maka koneksi akan berpindah ke backup. Hasil ping yang didapat dalam uji coba ketika jalur berpindah adalah 21ms; dan hanya terjadi dua kali unreachable, sedangkan untuk trafik browsing tidak mengalami kendala pada jaringan.Keywords: Internet; Jaringan failover; Open Shortest Path First; Algoritme Djikstra